La Violencia Familiar y su influencia en el Proceso de Enseñanza Aprendizaje de los Niños y Niñas de la Escuela “24 de Mayo” de la Ciudad de Loja y la Intervención del Trabajador Social - Banegas Quezada, Rober Hernán (2016)
The Family violence is any act or omission committed by a family member in relation to power, regardless of the physical space where it occurs that harms the well-being, physical and psychological integrity, or liberty and the right to full development of another family member. The research called "Family violence and its influence on the process of learning of children from school" 24 May "of the city of Loja and intervention Social Worker" allows to know the reality of children who they are victims of psychological and physical violence by their parents. The research process was based on field work and support of a broad theoretical scientific content enabling explain categories like; family, family violence, causes and consequences of family violence, teaching-learning process, focused from the process of involvement of family violence; and finally roles, functions and intervention Social Worker. Identifying the research question he was raised as targets; identify how domestic violence affects the process of learning of children, verifying the existence of the same family in their homes, and their involvement in the teaching-learning process; to finally design a proposal for social action that contributes to strengthen family relationships that may decrease the rate of violence of those who are educated in school "24 May" of the city of Loja. For the development of research scientific method used it to decipher and sort different categories of analysis of the object of study, and complementary methods such as was used: inductive-deductive method which allowed us to know the general problems to reach individuals ; analytical method that was used to perform the analysis of results, statistical method, allowed by tables and bars represent the percentages obtained in the tools and techniques used for gathering information, same as facilitated verification and compliance objectives From the results obtained in the research are among the main findings, family violence against children generated in homes by their parents, focusing on 5 the development of problems such as; underperforming, low self-esteem, behavioral problems, inadequate vocabulary, unwillingness of attention, decadent interpersonal relationships with peers, little interest in learning etc. Conflicts that limit children a teaching proper training; same that occur due to various factors, among them are bad family relationships, poor communication between parents, low income, alcohol consumption, or by parents who were abused in childhood (according to the survey of parents ) etc. Taking into consideration the findings in the investigation findings and recommendations arising Faced with this situation as a future Social Worker Social Intervention proposal is presented for the benefit of children who are violated in their